Bridging the communication gap in agrometeorological services: Enhancing the uptake and effectiveness for users in developing countries - Vieri Tarchiani; Sebastian Grey (Climate Services)
Over the past decades, advancements in agrometeorological monitoring and forecasting have been driven by technology, infrastructure, and capacity building. Literature highlights that agrometeorological services support agricultural decision-making, boosting farmers’ resilience and income globally. However, challenges in communication and dissemination limit their effectiveness, particularly for smallholder farmers in remote areas. The problem extends beyond media type and format to issues of accessibility, comprehensibility, and users’ trust. While technology has enabled faster dissemination, there is a risk of new services being technology-centered rather than user-focused. This non-systematic literature review delves into effective communication strategies for agrometeorological information in developing countries, reviewing existing knowledge and presenting case studies. It addresses how to ensure access to information, identify efficient communication channels, use inclusive technologies, enhance users’ understanding, make information actionable, and gather feedback on information effectiveness. Stakeholders’ engagement methods include a variety of participatory approaches and iterative monitoring, evaluation and learning processes. The choice of communication channels significantly affects information reach. Despite the rise of ICT, challenges in access and understanding persist, especially for marginalized groups, making simple communication technologies like rural radios still crucial for last-mile dissemination. The review emphasizes that no single communication approach fits all situations. Key principles of coproduction and user engagement in climate services are essential for effective agrometeorological communication. Future directions include enhancing the legitimacy and salience of services by integrating local knowledge, expanding scope to include herders and off-farm stakeholders, building capacity among intermediaries and users, soliciting feedback, and fostering public–private partnerships for scaling and sustainability.